Toxicity of Pyrethroid and Organophosphorous Insecticides against Two Field Collected Strains of the German Cockroach Blattella germanica (Blattaria: Blattellidae) from Hospitals in Hamadan, Iran - Mojtaba Limoee; Behroz Davari; Seyed Hassan Moosa-Kazemi (Tehran University of Medical Sciences, 2015)
Background: The German cockroach, Blattella germanica is a major hygienic pest and mechanical vector for path- ogenic agents in hospitals and residential areas. The development of insecticide resistance is a serious problem in controlling of this pest. Toxicity of four commonly used insecticides (permethrin, cypermethrin, malathion and chlorpyrifos) against two hospital- collected strains of the German cockroach was investigated. Methods: Topical bioassay methods were carried out for detecting insecticide susceptibility of adult male cock- roaches. For each insecticide, four to six concentrations resulting in >0% and <100% mortality were used. Three to six replicates of 10 cockroaches per concentration were conducted. The differences between LD50 (µ g/g) values were considered statistically significant only when the 95% confidence intervals did not overlap Results: Two hospital- collected strains of the German cockroach showed low to moderate levels of resistance to chlorpyrifos, permethrin, malathion and cypermethrin based on resistance ratios compared with susceptible strain. Conclusion: The low level chlorpyrifos resistance suggesting this insecticide may still provide adequate control of these strains. While the obsereved moderate levels of resistance to cypermethrin could imply developing resistance to this compound.